Kebudayaan Islam dalam era globalisasi: Adaptasi dan transformasi - Khadafi, Muamar; Ghozi, Ahmad; Alana, Wahyu Fathin; Khidir, Muhammad Ali (Maliki Interdisciplinary Journal, 2024)
This research aims to examine how Islamic culture adapts and transforms in the era of globalization. The primary focus of this study is to identify the patterns of cultural adaptation undertaken by Muslim communities, as well as to understand the processes of transformation occurring in various aspects of Islamic culture, including art, education, law, and daily life. The research will also explore the role of digital technology in mediating and disseminating Islamic culture, and its impact on the cultural identity of Muslims worldwide. This can result in the exchange of ideas, values, and practices between Muslim and non-Muslim communities, thereby shaping complex cultural dynamics. While there are challenges in maintaining the authenticity and integrity of Islamic culture amidst the rapid currents of globalization, there are also opportunities to broaden the understanding and experiences of Muslims through interactions with other cultures.